Characterization of the β-adrenoceptor subtype involved in mediation of glucose transport in L6 cells - Nevzorova, Julia (2002)
1. The receptor that mediates the increase in glucose transport (GT) in response to β-adrenoceptor (β-AR) agonists was characterized in the rat skeletal muscle cell line L6, using the 2-deoxy-[(3)H]-D-glucose assay. 2. The β(3)-AR agonist BRL37344 (pEC(50)=6.89±0.21), the β-AR agonist isoprenaline (pEC(50)=8.99±0.24) and the β(2)-AR agonist zinterol (pEC(50)=9.74±0.15) increased GT as did insulin (pEC(50)=6.93±0.15). The highly selective β(3)-AR agonist CL316243 only weakly stimulated GT. 3. The pK(B) values calculated from the shift of the pEC(50) values of the agonists in the presence of the β(1)-AR selective antagonist CGP 20712A or the β(3)-AR selective antagonist SR 59230A were not indicative of activation of β(1)- or β(3)-ARs. Only (−)-propranolol and the β(2)-AR selective antagonist ICI 118551 caused marked rightward shifts of CR curves to isoprenaline (pK(B)=10.2±0.2 and 9.6±0.3), zinterol (pK(B)=9.0±0.1 and 9.4±0.3) and BRL 37344 (pK(B)=9.4±0.3 and 8.4±.2), indicating participation of β(2)-ARs. 4. The pharmacological analysis was supported by reverse transcription and polymerase chain reaction analysis of L6 mRNA, which showed high levels of expression of β(2)-AR but not β(1)- or β(3)-AR in these cells. 5. Forskolin and dibutyryl cyclic AMP produced negligible increases in GT while the phosphatidylinositol-3 kinase inhibitor, wortmannin, significantly decreased both insulin- and zinterol-stimulated GT, suggesting a possible interaction between the insulin and β(2)-AR pathways. 6. This study demonstrates that β(2)-ARs mediate the increase in GT in L6 cells to β-AR agonists, including the β(3)-AR selective agonist BRL 37344. This effect does not appear to be directly related to increases in cyclic AMP but requires P13K.